Erythrocyte-Derived microRNAs: Emerging Players in Cardiovascular and Metabolic Disease. Issue 5 (27th April 2023) - Kontidou, Eftychia; Collado, Aida; Pernow, John; Zhou, Zhichao
Abstract : Recent studies have demonstrated a novel function of red blood cells (RBCs) beyond their classical role as gas transporters, that is, RBCs undergo functional alterations in cardiovascular and metabolic disease, and RBC dysfunction is associated with hypertension and the development of cardiovascular injury in type 2 diabetes, heart failure, preeclampsia, familial hypercholesterolemia/dyslipidemia, and COVID-19. The underlying mechanisms include decreased nitric oxide bioavailability, increased arginase activity, and reactive oxygen species formation. Of interest, RBCs contain diverse and abundant micro (mi)RNAs. miRNA expression pattern in RBCs reflects the expression in the whole blood, serum, and plasma. miRNA levels in RBCs have been found to be altered in various cardiovascular and metabolic diseases, which contributes to the development of cardiovascular complications. Evidence has shown that RBC-derived miRNAs interact with the cardiovascular system via extracellular vesicles and argonaute RISC catalytic component 2 as carriers. Alteration of RBC-to-vascular communication via miRNAs may serve as potential disease mechanism for vascular complications. The present review summarizes RBCs and their released miRNAs as potential mediators of cardiovascular injury. We further focus on the possible mechanisms by which RBC-derived miRNAs regulate cardiovascular function. A better understanding of the function of RBC-derived miRNAs will increase insights into the disease mechanism and potential targets for the treatment of cardiovascular complications.